The Effect of Implementation of Government Accounting Standards, Human Resource Competencies, and Internal Control on the Quality of Local Government Financial Statements (Empirical Study of Bone Regency Government) - Andi Alvian Agsyam Saputra; Muhyarsyah (IAEI, 2023)
The purpose of this study was to examine: (1) The effect of Government Accounting Standards, (2) The Effect of Competence of Human Resources, (3) The Effect of Internal Control on the quality of local government financial reports. The population in this study is the SKPD of the Bone Regency Government in the Treasurer or Financial Reporting section. The sampling technique used in this research is saturated sampling. The data analysis method used is descriptive assumption test, classic assumption test, classic assumption test, and multiple linear regression analysis test. The results of the analysis show that government accounting standards and internal control have a positive effect on the quality of local government financial reports, while human resource competencies have no effect on the quality of local government financial reports.